OBSERVATION OF THE DECAY K0L-]E+E-E+E- - Barr, G; Carosi, R; Coward, D; Cundy, D; Doble, N; Gatignon, L; Gibson, V; Grafstrom, P; Hagelberg, R; Vanderlans, J; Nelson, H; Wahl, H; et al. (1991)
Several 14 Ω-e+ pairs of which 11.4±3.8 are consistent with the decay Ωc0→ Ω-e+ve were reconstructed. The probability that a background fluctuation was observed is 7.6×10-5. The measured Β·σ is (42.2±14.1±5.7) fb.